2022
DOI: 10.3390/cancers14051148
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Seropositivity and Viral DNA in Breast Tumors Are Associated with Poor Patient Prognosis

Abstract: Human cytomegalovirus (HCMV) infects 40–70% of adults in developed countries. Detection of HCMV DNA and/or proteins in breast tumors varies considerably, ranging from 0–100%. In this study, nested PCR to detect HCMV glycoprotein B (gB) DNA in breast tumors was shown to be sensitive and specific in contrast to the detection of DNA for immediate early genes. HCMV gB DNA was detected in 18.4% of 136 breast tumors while 62.8% of 94 breast cancer patients were seropositive for HCMV. mRNA for the HCMV immediate earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…We previously published, in a smaller cohort, that patients with a low-grade HCMV-IE infection in primary colon and breast cancers have significantly longer time to brain metastasis and OS [ 35 ]. Other researchers have also reported an association between the risk of developing metastasis in patients with breast cancer who are seropositive for HCMV or HCMV DNA positive [ 52 ]. Furthermore, HCMV was correlated to a shorter relapse free survival in patients with breast cancer [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously published, in a smaller cohort, that patients with a low-grade HCMV-IE infection in primary colon and breast cancers have significantly longer time to brain metastasis and OS [ 35 ]. Other researchers have also reported an association between the risk of developing metastasis in patients with breast cancer who are seropositive for HCMV or HCMV DNA positive [ 52 ]. Furthermore, HCMV was correlated to a shorter relapse free survival in patients with breast cancer [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported in 2 studies higher prevalence of HCMV IE DNA and protein expression in CRC and breast cancer and their metastases to the brain with poor outcome [ 30 , 31 ]. Recently, two studies reported that HCMV gB DNA detection or expression of HCMV IE in breast cancer was found to be associated with shorter survival [ 32 , 33 ]. HCMV IE and E proteins were always detected in the cytoplasm in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cytomegalovirus has been reported as a risk factor for glioma, neuroblastoma, as well as breast cancer [3,4,[71][72][73][74]. Persons suffering from breast cancer who were CMV-seropositive or had CMV DNA in tumor tissue were significantly more likely to develop Stage IV metastatic tumors, hinting at an adverse oncomodulatory role of the virus, which promotes metastases [75]. An adverse effect of CMV was also noted elsewhere regarding the same pathology [76].…”
Section: Arguments In Favor Of CMV Oncogenesismentioning
confidence: 95%